Geophysical characteristics of the continental crust along the Lithoprobe Eastern Canadian Shield Onshore–Offshore Transect (ECSOOT): a review - Hall, Jeremy; Louden, Keith E; Funck, Thomas; Deemer, Sharon (Canadian Journal of Earth Sciences, 2002)
The Eastern Canadian Shield OnshoreOffshore Transect (ECSOOT) of the Lithoprobe program included 1200 km of normal-incidence seismic profiles and seven wide-angle seismic profiles across Archean and Proterozoic rocks of Labrador, northern Quebec, and the surrounding marine areas. Archean crust is 3344 km thick. P-wave velocity increases downwards from 6.0 to 6.9 km/s. There is moderate crustal reflectivity, but the reflection Moho is unclear. Archean crust that stabilized in the Proterozoic is similar except for greater reflectivity and a well-defined Moho. Proterozoic crust has similar or greater thickness, variable lower crustal velocities, and strong crustal reflectivity. Geodynamic processes of Paleoproterozoic growth of the Canadian Shield are similar to those observed in modern collisional orogens. The suturing of the Archean Core Zone and Superior provinces involved whole-crustal shearing (top to west) in the Core Zone, linked to thin-skinned deformation in the New Quebec Orogen. The Torngat Orogen sutures the Nain Province to the Core Zone and reveals a crustal root, in which Moho descends to 55 km. It formed by transpression and survived because of the lack of postorogenic heating. Accretion of the Makkovik Province to the Nain Province involves delamination at the Moho and distributed strain in the juvenile arcs. Delamination within the lower crust characterizes the accretion of Labradorian crust in the southeastern Grenville Province. Thinning of the crust northwards across the Grenville Front is accentuated by Mesozoic extension that reactivates Proterozoic shear zones. The intrusion of the Mesoproterozoic Nain Plutonic Suite is attributed to a mantle plume ponding at the base of the crust.